Terrorist groups' use of media and social networking sitesThe war on Syria as a model (Damascus University Journal for the economic and Political sciences, 2025)
The current study aimed to investigate the degree to which terrorist groups employ the media and social networking sites in the war on Syria by analyzing a set of data by adopting the descriptive analytical approach. Psychological), the research was applied to an intentional sample of (85) male and female students enrolled in the first and second year at the College of Media, Damascus University.The data was analyzed using the statistical package processing program (SPSS), where the study concluded the following results:The study sample members’ estimates of terrorist groups’ use of the media and social networking sites in the war on Syria for the purpose of communication came to a high degree.The study sample members’ estimates of terrorist groups’ use of the media and social networking sites in the war on Syria for the purpose of propaganda came to a high degree.The study sample members’ estimates of terrorist groups’ use of the media and social networking sites in the war on Syria for the purpose of psychological impact came to a high degree.The study sample members’ estimates of terrorist groups’ use of the media and social networking sites in the war on Syria came to a high degree.
Keywords: Terrorism; Media; Social Networking Sites